If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = -2(3p + 3) Reorder the terms: 6 = -2(3 + 3p) 6 = (3 * -2 + 3p * -2) 6 = (-6 + -6p) Solving 6 = -6 + -6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6p' to each side of the equation. 6 + 6p = -6 + -6p + 6p Combine like terms: -6p + 6p = 0 6 + 6p = -6 + 0 6 + 6p = -6 Add '-6' to each side of the equation. 6 + -6 + 6p = -6 + -6 Combine like terms: 6 + -6 = 0 0 + 6p = -6 + -6 6p = -6 + -6 Combine like terms: -6 + -6 = -12 6p = -12 Divide each side by '6'. p = -2 Simplifying p = -2
| 2y+13=2y+19 | | 350x+xy-200=0 | | c+-102=277 | | -4x-4=32 | | -p-4=2 | | -0.26=log(x) | | 11-3f=2 | | 3.8/4 | | -8x^2+3-10x=0 | | 5(-4x+7)=175 | | m+-77=-50 | | -p+2=-3 | | -3c=-81 | | -75=v-83 | | 8x-4=2x+8+x | | p+20=32 | | (11x^2+7x-14)(x)= | | 2(x+6)+3=3x+4-2x+4 | | 84=w/6 | | 13.95d+1.95=85.65 | | n/8=-17 | | 6x(7x-8)-2(21x-6)=3-30x | | 13.95+1.95=85.65 | | (8+7)+(9+2)=18 | | v+-607=-907 | | (4x)(4x)-16x-9=0 | | 60000+80000=2x+x | | b/-1=-0.51 | | (x^3-2x+3)-(3x^2+4x-3)= | | g+99=-464 | | 184=2(w+20)+2w | | X^2+4=8-8 |